2010
DOI: 10.1103/physreva.81.042104
|View full text |Cite
|
Sign up to set email alerts
|

Decoherence in a double-slit quantum eraser

Abstract: We study and experimentally implement a double-slit quantum eraser in the presence of a controlled decoherence mechanism. A two-photon state, produced in a spontaneous parametric down conversion process, is prepared in a maximally entangled polarization state. A birefringent double-slit is illuminated by one of the down-converted photons, and it acts as a single-photon two-qubits controlled not gate that couples the polarization with the transversal momentum of these photons. The other photon, that acts as a w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
1
18
0
2
Order By: Relevance
“…Indeed, recent experiments in CO 2 have shown that interference effects stemming from the core dynamics are only relevant if the structural minimum provides a window for them to be observed. For high enough intensities, the energy position of the dynamical minimum lies outside this window and can no longer be observed [35]. This is in agreement with the experimental findings in [36], which support the structural instead of the dynamical interference picture, and with the computations in [37], which show that multielectron effects are important in the cutoff, but not in the mid-plateau energy region.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, recent experiments in CO 2 have shown that interference effects stemming from the core dynamics are only relevant if the structural minimum provides a window for them to be observed. For high enough intensities, the energy position of the dynamical minimum lies outside this window and can no longer be observed [35]. This is in agreement with the experimental findings in [36], which support the structural instead of the dynamical interference picture, and with the computations in [37], which show that multielectron effects are important in the cutoff, but not in the mid-plateau energy region.…”
Section: Discussionsupporting
confidence: 90%
“…This allows us to prepare and measure a more general class of path qudit states. Each PM has an internal polarizer used to align the photon polarization state such that in the interferometer there is no path information available [83,84], which would compromise the visibility of the observed interference. Fiber-based polarization controllers (not shown) are used in each path to maximize transmission through the PMs.…”
Section: Multi-arm Interferometers Based On Multi-core Fibersmentioning
confidence: 99%
“…For example, if one measures the distribution P (x), then the distributions P (n) and P (r) can be calculated directly using definitions (6). The same is true for the momentum variables.…”
Section: Measuring Modular Variablesmentioning
confidence: 99%
“…The early discussions between Bohr and Einstein concerning the validity of the complementarity principle and wave-particle duality centered around the appearance (or not) of double-slit interference when one attempts to mark the passage of the particle through the slits [1]. Later, it was shown that the entanglement between the particles and a quantum "which-path" marker allows one to register the passage of the particle through the double slit and subsequently erase that information, recovering an interference pattern [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation